Korekta i rozwój potencjału w zakresie komunikowania: modelowanie osobowościowe, konstrukty, nastolatkowie = Correction and developing potential of the communicative modelling of teenagers' personality constructs - Tokareva, Natalia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents a functional model of communicative modelling of teenagers' rational personality constructs under the specially designed conditions of the educational process. The theoretical and methodological concepts of the implementation of this model in the context of the system and integrative scientific paradigm and genetic and modelling method were considered.
Keywords: komunikatywne modelowanie; konstrukty osobowościowe; system integracyjny paradygmatu; metoda genetyczna modelowania; interakcja odblaskowa dialogiczna; communicative modelling; personal constructs; system and integrative paradigm; genetic and modelling method; reflective and dialogical interaction